2007
DOI: 10.1021/jp0658804
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Phase-Change Nanostructure:  Germanium Telluride Nanowire

Abstract: High-quality nanowires of germanium telluride (GeTe), a one-dimensional chalcogenide phase-change nanostructure, were synthesized via thermal evaporation method under vapor−liquid−solid mechanism. The physical morphology, chemical composition, and crystal structure of the as-synthesized GeTe nanowires were investigated by scanning electron microscopy, energy dispersive X-ray spectroscopy, high-resolution transmission electron microscopy (HR-TEM), and X-ray photoemission spectroscopy. Through real-time TEM imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 27 publications
4
97
2
Order By: Relevance
“…3 revealed that core STNWs started to melt at the one third temperature of the melting point of bulk ST (621 1C) [17]. It is well known that the melting point of low-dimensional materials is lower than that of bulk materials due to the size-effect [18,19]. This is the first observation of the lower melting temperature of STNWs, and indicates that they might be used in fabricating SONTs at low temperature.…”
Section: Resultsmentioning
confidence: 98%
“…3 revealed that core STNWs started to melt at the one third temperature of the melting point of bulk ST (621 1C) [17]. It is well known that the melting point of low-dimensional materials is lower than that of bulk materials due to the size-effect [18,19]. This is the first observation of the lower melting temperature of STNWs, and indicates that they might be used in fabricating SONTs at low temperature.…”
Section: Resultsmentioning
confidence: 98%
“…entire networks of switchable structures are used. They can frequently be deposited right on top of electron transparent membranes as parts of TEM sample grids without any need for careful placement (Avizienis et al, 2012;Liang et al, 2014;Sun et al, 2007). Alternatively, the nanowires can be randomly dispersed and the electrodes are deposited and shaped in a later stage with lithographic means (Chiang et al, 2011).…”
Section: Location Unspecific Sample Preparationmentioning
confidence: 99%
“…In terms of TEM analysis these devices are advantageous because they forestall the need for complicated and time-consuming crosssectional specimen preparation if deposited directly onto electron transparent membranes. Horizontal memristive devices have been realized with switching nano-structures containing Ag wires (Avizienis et al, 2012), CuO nanowires (Fan et al, 2013;Liang et al, 2014), ZnO nanowires (Chiang et al, 2011), TiO 2 (Lin et al, 2016), Cu 2 S nanowires (Liu et al, 2015), GeTe nanowires (Sun et al, 2007), and Ge/Si nanowires (Yan et al, 2011). The large variety of material systems analyzed underlines the flexibility and relative ease with which such investigations can be conducted.…”
Section: Memristive Nanostructuresmentioning
confidence: 99%
“…It provides the potential for high scaled phase change memory devices and multilevel memory applications. Single-crystal nanowires based on different phase change materials such as GeTe [2][3][4][5][6],GeSb [7], Ge 2 Sb 2 Te 5 [8][9][10][11], Ge 1 Sb 2 Te 4 [12] and In 2 Se 3 [13] have been previously synthesized and demonstrated a nano-second level switching time at very low powers, suggesting that the nanowires could be ideal for data storage devices.…”
Section: Introductionmentioning
confidence: 99%